Remote vocational learning opportunities—A comparative eye‐tracking investigation of educational 2D videos versus 360° videos for car mechanics. (28th August 2021) - Hekele, Felix; Spilski, Jan; Bender, Simon; Lachmann, Thomas
Abstract: This study utilises a novel approach to investigate the effectiveness of different learning modalities by combining video‐based learning with eye‐tracking. An excerpt taken from a vocational education instruction for car mechanics was videotaped using two different cameras: a standard 2D video camera and a professional 360° camera. The video recorded with the 2D camera was presented on a tablet, with a fixed angle, whereas the video recorded with the 360° camera was presented as non‐interactive 3DoF virtual reality (nVR) environment using a head‐mounted display. In both conditions, participants' fixation patterns were recorded and analysed in conjunction with a set of standardised questionnaires. Participants ( N = 48) were randomly assigned to either the 2D‐video group or the nVR group, with 23 participants in the 2D‐video and 25 participants in the nVR group. The task of the participants in both groups was to watch the educational video while wearing an eye‐tracker and then complete a standardised test on the presented content. The eye‐tracking data indicated that participants in the nVR group showed longer total fixation durations on the instructor, but not other areas of interest, compared to the 2D video group. The standardised test indicated no differences in learning outcome between the groups. Implications from the current study as well as limitations and a outlook for further research will be discussed. Practitioner notes What is already known about this topic Virtual reality (VR) technology is getting more commonplace in educational settings. It is unclear whether VR‐based learning holds clear benefits over more traditional approaches such as hands‐on‐training or video‐based learning. What this paper adds This paper adds a comparison of two common video‐based teaching techniques and compares them in respect to learning outcome and learner's attention. The novelty of the current paper is the addition of eye‐tracking in both tablet‐based and HMD‐based learning scenarios to investigate learners' visual attention. Describes potential attention benefits of 360° videos compared to 2D videos despite no differences in learning outcome directly. Implications for practice and/or policy Results highlight the potential of placing more focus on social factors in 360° video material. Future 360° videos and VR environments can add additional focus on instructors or other socially relevant aspects to foster student learning and engagement.